Strategi Pengembangan Kurikulum Tingkat Lembaga Pendidikan Berbasis Moderasi Beragama di Madrasah Ibtidaiah Al-Asyhar Malang - A. Qomarudin; Roihatul Jannah (Evaluasi : Jurnal Manajemen Pendidikan Islam, 2025)
Islamic educational institutions must be serious in producing students who have a moderate attitude in practicing religion, so it is important to conduct an in-depth study of the systematic efforts of educational institutions carried out by MI Al-Asyhar Malang, both related to the integration of religious moderation values in the development of educational curriculum and related to the forms of activities in implementing programs that emphasize strengthening the values of religious moderation. This study utilizes a qualitative approach with a case study type, and uses interview, observation, and documentation data collection techniques. The results of this study indicate that 1) the integration of religious moderation values is described in the development of a curriculum that focuses on intracurricular, co-curricular, and extracurricular; and 2) the institution carries out several activities that can strengthen the values of religious moderation, including integrated learning, flag ceremonies, commemoration of religious holidays, social services, scouting activities, competitions, and the habituation of commendable attitudes.